The Bisnis Indonesia Newspaper Gets Revenue Stream in Convergence - Irsad Irsad; Suyanto Suyanto; Yasir Yasir (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
Convergence as a model of newspaper mediamorphosis has been carried out since 1995 or a year after the internet entered Indonesia. Bisnis Indonesia started its convergence by launching Bisnis.com in 2006. This study aims to find out the dynamics faced by Bisnis Indonesia in maintaining the firewall, which is the ethics of journalism in commercialization. This is related to media convergence that tends to strengthen the capitalist character of the media. The research method was carried out with a qualitative approach, where the data collection technique was triangulation. The researchers interviewed ten informants from the management and two from customers using the purposive sampling technique. Internal informants range from the president director, editor-in-chief, and reporters. This study finds that convergence can be a solution for Bisnis Indonesia to get out of circulation problems and find revenue to continue their media business. However, it becomes a challenge to maintain the independence of the newsroom.